1977
DOI: 10.1111/j.1365-2559.1977.tb01653.x
|View full text |Cite
|
Sign up to set email alerts
|

Monophasic synovial sarcoma–a histological entity?

Abstract: Consideration is given to the concept of a histologically identifiable monophasic type of synovial sarcoma. It is accepted that a sarcomatous tumour may be encountered where the spindle cells assume a somewhat epithelioid appearance associated with a reticulin pattern unlike that of most other spindle cell sarcomas. The appearance should alert a hsitopathologist to the possibility of a synovial sarcoma and prompt the examination of multiple additional sections in an attempt to find the pathognomonic biphasic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 6 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…The diagnosis of SS of the head and neck is particularly difficult due to the rare occurrence of the tumor in this region and its resemblance to other tumors occurring more frequently in the head and neck. SSs are histologically divided into two subgroups: biphasic SS, characterized by the admixture of spindle and epithelioid cells, the latter often organized in gland-like structures, and monophasic SS, in which only one cell component, either spindle or, less often, epithelioid, is present 7,[9][10][11][12] . Biphasic SS needs to be distinguished from a carcinoma with partial sarcomatoid differentiation, while monophasic spindle cell SS requires a differential diagnosis with all spindle cells tumors, including hemangiopericytoma, malignant schwannoma, and spindle cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of SS of the head and neck is particularly difficult due to the rare occurrence of the tumor in this region and its resemblance to other tumors occurring more frequently in the head and neck. SSs are histologically divided into two subgroups: biphasic SS, characterized by the admixture of spindle and epithelioid cells, the latter often organized in gland-like structures, and monophasic SS, in which only one cell component, either spindle or, less often, epithelioid, is present 7,[9][10][11][12] . Biphasic SS needs to be distinguished from a carcinoma with partial sarcomatoid differentiation, while monophasic spindle cell SS requires a differential diagnosis with all spindle cells tumors, including hemangiopericytoma, malignant schwannoma, and spindle cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In the large majority of cases, this applies to the spindle cell sarcomatous component, which is easily misdiagnosed as fibro sarcoma, hemangiopericytoma or some other spindle cell neoplasm by the unwary. 9,10 Histopathological examination of the excised mass from our patient revealed cellular lesion composed of sheets and fascicles of spindle cells with indistinct cytoplasm, irregular nuclear membrane, mild pleomorphism, open chromatin and prominent nucleoli. Foci of necrosis, haemorrhages were seen but there was no evidence of vascular emboli.…”
Section: Discussionmentioning
confidence: 84%
“…15) quite common in the typical biphasic synoviai sarcomas (Roth et al, 1975;Evans, 1980;Schmookler, Enzinger & Brannon, 1982, Varela-Duran & Enzinger, 1982 and (ii) the presence of focal calcification, again not unusual in the typical case (Crocker & Stout, 1959;Cadman et a/., 1965;Varela-Duran & Enzinger, 1982). MacKenzie (1977), however, showed that, by careful exaniination of so-called monophasic tumours, features of a developing biphasic pattern can be identified, especially with the use of a reticulin stain; and if, as a consequence, further sections of the tumour are cut then the typical biphasic pattern v^-ill be revealed. Other authors have similarly felt that a careful search will reveal an epithelioid component, thus verifying the diagnosis (Roth et al, 1975;Schmookler et al, 1982;Varcla-Duran & Enzinger, 1982).…”
Section: Synoviai Sarcomamentioning
confidence: 98%